Analisis Efektivitas Program Keluarga Berencana dalam Pengendalian Pertumbuhan Penduduk di DP3AKKB Provinsi Banten - Resma Cahya Fatimah; Gatot Hartoko; Eli Apud Saepudin (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The Family Planning (FP) Program is a strategic government policy aimed at controlling population growth, improving family welfare, and supporting sustainable development. In Banten Province, the implementation of the program continues to face challenges, including unequal access to family planning services, low male participation, and variations in contraceptive use across districts. This study aims to analyze the effectiveness of the Family Planning Program in controlling population growth at the Women's Empowerment, Child Protection, Population and Family Planning Office (DP3AKKB) of Banten Province. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, documentation, and literature review. Data were analyzed using data reduction, data display, and conclusion drawing, supported by source and method triangulation to ensure validity. The findings indicate that the program has contributed to increasing contraceptive prevalence, strengthening reproductive health education, and enhancing coordination among stakeholders in population management. However, program effectiveness is still constrained by limited human resources, unequal service accessibility, and insufficient public awareness regarding family planning. Strengthening the capacity of field officers, expanding digital-based family planning services, and improving collaboration between government institutions, health providers, and communities are essential to enhance the effectiveness and sustainability of population control efforts in Banten Province.